The Judiciary as Bulwark of the Rule of Law and Democracy in Nigeria - Ishmael U. Gwunireama (Activa Yuris: Jurnal Hukum, 2021)
Democracy, especially constitutional democracy, rests on the rule of law, which rests on the legislature, executive and judiciary tripod. Nigeria has adopted these principles since independence to date, although with military interregnums. The roles of the legislature and executive are often highlighted partly because of electioneering procedures of the manifesto (propaganda), voting, among others. The contrary is the case with the judiciary, which appears to be in the background but plays very pivotal roles in preserving the rule of law and democracy principles. It does not issue manifestoes; it neither campaigns nor seeks election and does not hold constituency meetings. As a result, its roles in engendering the rule of law and democracy in Nigeria are less known. With the aid of decided cases, this work contends that the judiciary is indeed the bulwark of the rule of law and democracy. Therefore, those trampling on the judiciary, especially its independence should be cautious to know that but for the judiciary the minimal progress Nigeria has made in implementing the principles of rule of law and democracy would not have been achieved in the face of the excesses of the legislature and executive. In the same vein, the judiciary must purge itself and be of high moral turpitude to effectively play these sacred roles.